PENGARUH HARGA DAN KEMASAN TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO INICAKE BROWNIES - Siti Aisyah; Uus Mohammad Darul Fadli (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
The competition in the culinary brownies business is getting tougher for it requires a special strategy so that consumers still decide to buy inicake brownie. The study aims to analyze the influence of price and packaging on Inicake Brownis consumer purchasing decisions. The research method used is quantitative with data collection techniques through surveys. The data obtained is analyzed using double linear regression. Research results show that prices have a significant influence on purchasing decisions, while packaging has no significant impact. This means that consumers consider prices more than packaging in making purchasing decisions.